2019
DOI: 10.1136/bmjopen-2019-031649
|View full text |Cite
|
Sign up to set email alerts
|

Journey to multimorbidity: longitudinal analysis exploring cardiovascular risk factors and sociodemographic determinants in an urban setting

Abstract: ObjectiveTo study the social determinants and cardiovascular risk factors for multimorbidity and the acquisition sequence of multimorbidity.DesignLongitudinal study based on anonymised primary care data.SettingGeneral practices in an urban multiethnic borough in London, UK.Participants332 353 patients aged ≥18 years.Main outcome measuresClinical and sociodemographic characteristics of patients with multimorbidity, defined as ≥3 of 12 long-term conditions (LTCs) selected according to high predicted healthcare u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(135 citation statements)
references
References 17 publications
(25 reference statements)
5
128
1
1
Order By: Relevance
“…This would be the case of hypertension, which was strongly associated with multimorbidity upon follow-up in our sample. A study addressing 332 thousand subjects in England also reported hypertension as a very strong predictor for multimorbidity [15]. Hypertension prevention, along with securing effective treatment for these patients, would be needed to improve the overall health of the population, and reduce multimorbidity burden.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…This would be the case of hypertension, which was strongly associated with multimorbidity upon follow-up in our sample. A study addressing 332 thousand subjects in England also reported hypertension as a very strong predictor for multimorbidity [15]. Hypertension prevention, along with securing effective treatment for these patients, would be needed to improve the overall health of the population, and reduce multimorbidity burden.…”
Section: Tablementioning
confidence: 99%
“…This preliminary finding may suggest that not all diabetic patients are at higher risk of multimorbidity, indicating that there may be some diabetes clusters with higher/lower risk. Likewise, another cohort study signaled hypertension, obesity and smoking as multimorbidity risk factors; nonetheless, diabetes was not identified as a risk factor [15].…”
Section: Tablementioning
confidence: 99%
“…The scientific literature has reached a consensus on the health harms of poverty-inequality. In their study of multimorbidity in the ethnically diverse London borough of Lambeth (where a third of a million are registered with a general practitioner (GP)), Ashworth et al 11 concluded that: 'acquisition of multimorbidity is patterned by socioeconomic determinants', with depression and asthma as early drivers of poor physical health. The US and the UK have similar high levels of inequality, and their inhabitants can expect to lose 7-9 healthy years (free from physical disability) by the age of 50 if they are poor, compared with their fellow citizens at the least deprived end of the gradient.…”
Section: What Are the Consequences Of Poverty-inequality?mentioning
confidence: 99%
“…In the US, white individuals were more likely to transition from ischaemic heart disease to death, while Asian and Native Hawaiian and Pacific Islander individuals were more likely to transition from diabetes to diabetes plus chronic kidney disease (Siriwardhana et al, 2018). In the UK, disease specific sequences /pathways also differed by ethnicity (Ashworth et al, 2019). For example, the white ethnic group was dominated by depression as a starting point, while diabetes was the most common starting point in the black ethnic group along with depression and serious mental illness.…”
Section: Association Analyses and Risk Factorsmentioning
confidence: 99%
“…Study, year Risk factors considered Findings of association analysis Ashworth et al (2019) Age, ethnicity, deprivation -Trajectories varied by age, ethnicity, and deprivation. For example, those in the least deprived quintile were more likely to start with DM and CHD.…”
Section: Table 5b Association Analysis and Risk Factors Of Multimorbmentioning
confidence: 99%